Empowering Teachers in the Digital Age: Leadership Strategies for Enhancing Pedagogic Competencies in High Schools - Mushadi, Mushadi; Usman, Nasir; Bahrun, Bahrun (Heca Sentra Analitika, 2025)
This study examines the strategies employed by school principals to enhance the digital pedagogic competencies of teachers in three public high schools in Kluet Utara, Aceh, Indonesia. With the growing demand for digital integration in education, effective leadership is critical in preparing teachers to utilize digital tools in classroom settings. Using a qualitative descriptive approach, data were collected over a two-month period through semi-structured interviews, direct observations, and document analysis. The findings revealed three main themes: (1) Professional Development Initiatives, (2) Infrastructure and Resource Allocation, and (3) Collaborative Practices. Professional development programs, such as workshops and training sessions, played a crucial role in developing foundational digital skills. Infrastructure investments in internet connectivity and digital resources facilitated digital integration, though resource limitations in some schools posed challenges. Collaborative practices, including peer mentoring and team-based problem solving, played a crucial role in fostering a supportive environment for digital teaching. However, teachers faced challenges related to varying levels of digital proficiency, time constraints, and limited resources. This study highlights the importance of a comprehensive, leadership-driven approach to developing digital competencies among teachers, suggesting that a combination of continuous professional development, adequate resources, and collaborative support can significantly enhance digital integration in schools. These findings underscore the necessity for educational leaders to adopt a comprehensive, multifaceted approach to building digital competencies among teachers. By strategically integrating continuous professional development, adequate infrastructure, and collaborative frameworks, school leaders can significantly accelerate digital transformation efforts. For policymakers, this research underscores the crucial importance of aligning educational policies with resource allocation and leadership training to facilitate systemic digital integration. In an increasingly digitalized educational landscape, such leadership-driven strategies are indispensable for achieving equitable and effective teaching outcomes on a broader scale.